Understanding the Role of Achievements in Game-Based Learning - Lucas Blair; Clint Bowers; Janis Cannon-Bowers; Emily Gonzalez-Holland (Serious Games Society, 2016)
The objective of the current research was to examine whether one potentially effective gaming strategy-achievements-has a positive impact on learning in a game-based environment. An achievement in a video game is a reward or recognition earned by players for an in-game accomplishment. This paper describes a series of studies to evaluate the effects of achievement types on learning in a game designed to teach about health resources. The Game "Phone Dash" was used as the testbed for the following studies. The following questionnaires were utilized in this study: Video Game Self-Efficacy Scale (VGSES) questionnaire, Relevance and Usefulness questionnaire, Game Engagement Questionnaire (GEQ), and the Intrinsic Motivation Inventory (IMI). Four studies were conducted. Results indicated that while in unison, the achievements were not as potent in motivating performance, certainly when combined they produced measurable changes in behavior. The four studies described in this paper provide important information regarding the optimal design of achievements in game-based health education. Developers of future game-based learning can use this information to enhance the potential effectiveness of their products.